Retinopathy of prematurity in a tertiary care center: A study of prevalence, risk factors, and outcomes - Kumar, K Lathiesh; Seeralar, A T Arasar; Kamalarathnam, C N (Indian Journal of Child Health, 2017)
Background: Retinopathy of prematurity (ROP) is a serious complication of prematurity treatment and can lead to blindnessunless recognized and treated early. Objectives: The objectives were to estimate the prevalence of ROP in preterm infants in theneonatal intensive care unit (NICU), to identify the risk factors which predispose to ROP, and to assess the outcome of these cases.Methodology: A retrospective screening survey was performed enrolling all premature neonates admitted to the NICU betweenJanuary and December 2016, with a gestational age of 32 weeks or less at birth and a birth weight of 1500 g or less. Infants whosegestational age was >32 weeks or birth weight was >1500 g were included if they were exposed to oxygen therapy for more than7 days. A total of 344 neonates had a retinal evaluation by indirect ophthalmoscopy from the fourth postnatal week and followedup periodically. Perinatal risk factors for ROP were assessed using univariate and multivariate analysis. Infants who progressedto Stage 3 ROP were given laser therapy. Results: Out of the studied 344 neonates, 66 (19.2%) developed ROP in one or botheyes; 36 (54.5%) cases had Stage 1, 18 (27.3%) cases Stage 2, and 12 (18.2%) cases had Stage 3 ROP. None had Stages 4 and5 ROP. The 12 cases diagnosed as ROP Stage 3 underwent LASER therapy. Univariate analysis showed a significant relationshipbetween the occurrence of ROP and gestational age (p=0.001), sepsis (p=0.004), oxygen therapy (p=0.018), and frequent bloodtransfusions (p=0.030). However, an insignificant relationship was found between the occurrence of ROP and factors such asgender, mode of delivery, birth weight, respiratory distress syndrome, patent ductus arteriosus, intraventricular hemorrhage,hypotension, phototherapy, and duration of oxygen therapy, mechanical ventilation, and continuous positive airway pressure.Gestational age, sepsis, oxygen therapy, and frequent blood transfusions remained significant variables after logistic regressionanalysis. Conclusion: The prevalence of ROP in this study was 19.2%; low gestational age, sepsis, oxygen therapy, and frequentblood transfusions were significant risk factors for ROP. LASER was effective in the treatment and decreasing the progression ofROP.